A Simple, Novel Prognostic Score in Platinum Sensitive Relapsed Ovarian Cancer. (August 2021) - Goenka, Luxitaa; Nakka, Thejeshwar; Dubashi, Biswajit; Kayal, Smita; Penumadu, Prasanth; Chaturvedula, Latha; Veena, Pampapati; Durairaj, Jayalakshmi; Ganesan, Prasanth
Abstract : Objectives: Epithelial ovarian cancer is one of the commonest gynecologic cancers and one with the highest mortality. This retrospective cohort study was done to identify predictors of outcomes in platinum-sensitive relapsed ovarian cancer patients (PS-ROC). Methods: Data regarding baseline characters, laboratory findings, therapeutic details and survival outcomes was obtained from the medical records of PS-ROC patients presented between January 2015 and December 2019. Prognostic score was constructed using factors which were significant on multivariate analysis to predict survival outcomes. Results: A total of 71 (PS-ROC) patients were included in the study with a median age of 50 years. Relapse treatment was either chemotherapy alone (n=53, 75%) or chemotherapy plus surgery (n=18, 25%). The estimated progression-free survival (PFS) and overall survival were 10 and 29 months, respectively. The overall response rate after treatment of relapse was 59%. Prognostic score was created with the 3 factors (each scoring 1 point) which were predictive of PFS (higher lymphocyte-monocyte ratio, longer platinum-free interval and secondary cytoreduction). Patients with low score (0, 1) had better PFS than those with higher score (2, 3) (13 vs. 7 mo [ P =0.0001]). Conclusions: A composite prognostic score could predict outcomes in PS-ROC and potentially identify a subgroup with very poor prognosis. Future studies with a greater number of patients are needed to validate these findings. This information could help tailor more intense therapies to the high-risk patients and attempt to improve outcomes and serve as stratification factors for prospective trials. Abstract : Supplemental Digital Content is available in the text.